2019
DOI: 10.1039/c9cc04336e
|View full text |Cite
|
Sign up to set email alerts
|

External oxidant-free oxidation/[3+2] cycloaddition/aromatization cascade: electrochemical synthesis of polycyclic N-heterocycles

Abstract: The extent of the electrochemical oxidative [3+2] cycloaddition/aromatization cascade can be regulated with the assistance of redox mediators. Isoquinolinium salts as alternative azomethine ylide precursors afforded fully aromatized N-heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…[59] In the first step, N-phosphonated THIQs 214 is converted into iminium intermediates 216 in the presence of photoredox catalysis system Ru(bpy) Cl The same year, Wang et al reported synthesis of polycyclic N-heterocycles 223 in moderate to high yields (56-91%) in the presence of N-hydroxyphthalimide (NHPI) as catalyst and Et 4 NBr as the electrolyte in MeOH as solvent at room temperature (Scheme 44). [60] For this purpose, a range of activated olephines 215 such as maleimides, unsaturated esters and ketones were reacted with N-substituted THIQs 220 under electrochemical conditions. In anode, the stepwise proton-coupled electron transfer of NHPI led to the formation of phthalimide N-oxyl…”
Section: N-substituted Thiqsmentioning
confidence: 99%
See 1 more Smart Citation
“…[59] In the first step, N-phosphonated THIQs 214 is converted into iminium intermediates 216 in the presence of photoredox catalysis system Ru(bpy) Cl The same year, Wang et al reported synthesis of polycyclic N-heterocycles 223 in moderate to high yields (56-91%) in the presence of N-hydroxyphthalimide (NHPI) as catalyst and Et 4 NBr as the electrolyte in MeOH as solvent at room temperature (Scheme 44). [60] For this purpose, a range of activated olephines 215 such as maleimides, unsaturated esters and ketones were reacted with N-substituted THIQs 220 under electrochemical conditions. In anode, the stepwise proton-coupled electron transfer of NHPI led to the formation of phthalimide N-oxyl…”
Section: N-substituted Thiqsmentioning
confidence: 99%
“…reported synthesis of polycyclic N ‐heterocycles 223 in moderate to high yields (56–91%) in the presence of N ‐hydroxyphthalimide (NHPI) as catalyst and Et 4 NBr as the electrolyte in MeOH as solvent at room temperature (Scheme 44). [60] For this purpose, a range of activated olephines 215 such as maleimides, unsaturated esters and ketones were reacted with N ‐substituted THIQs 220 under electrochemical conditions. In anode, the stepwise proton‐coupled electron transfer of NHPI led to the formation of phthalimide N ‐oxyl (PINO), whereas in cathode, MeOH was reduced to H 2 and methoxide anion.…”
Section: C1‐functionalization With Annulationmentioning
confidence: 99%
“…Wang and co‐workers reported a good method for electrochemical synthesis of polycyclic N ‐heterocycles 106 via an oxidation/[3+2] cycloaddition/aromatization cascade (Scheme ). Starting with tetrahydroisoquinolines 104 and alkenes 105 , and employing N ‐hydroxyphthalimide (NHPI) as a mediator, they obtained N ‐heterocycles 106 in good yields.…”
Section: Non‐metal‐catalyzed Electrosynthesis Reactionsmentioning
confidence: 99%
“…Later, the 21st century brings renaissance in the field of electrochemical synthesis due to its prime advantages of superior environment and economic acceptance over the traditional chemical and photochemical processes. Electrochemical synthesis has been widely used in C–H bond functionalization, C–C and C–N bond formation, and diverse electrochemical rearrangement protocols . Very recently, Li’s group reported the electrochemical generation of a stabilized azomethine ylide followed by cycloaddition toward the synthesis of polycyclic N -heterocycles . Followed by this work, Masson et al documented an electrochemical tandem radical trifluoromethylation of allylamines via 1,3-dipolar cycloaddition toward the construction of CF 3 containing imidazolines and oxazolidines .…”
Section: Introductionmentioning
confidence: 99%